A CASE STUDY ON THE OPERATION AND MARKETING STRATEGIES OF GROUP HOME IN JAPAN - Lin, Linda Lin-Chin; Lu, Shu-Fen; Huang, Chen-Zhen (International Journal of Application on Economics and Business, 2024)
This study uses the Sky Group Home case study method to understand the current status of the industrial environment where the case is located, and explore the development trends and business strategies of Japanese companies in the group home market. It also analyses the corresponding marketing strategies of the industry based on regional expansion points, so as to improve the competitiveness of the industry's regional channels and open up new markets for international group home development. In recent years, Taiwan's group homes have been gradually privatized, and Japan's implementation experience has a high degree of reference value for my country's policy construction and group homes. This study focuses on operating groups in Japan Company A of Home House is taken as the research object, and the standard policies and operating models for the establishment of Japanese group homes are discussed through literature. Company A is used to understand its operating model based on its service content and current operating conditions. Environmental analysis and marketing mix analysis are conducted to explore its market, management and Marketing strategy; Finally, use SWOT analysis to summarize A The current situation of the company and suggestions for the future development of the industry. The legal entity creates a daily life environment similar to home, adhering to the core concept of "serving users", focusing on personal uniqueness, and providing users with social care in a small unit. In Japan, group homes gather two major groups: the elderly and the physically and mentally disabled, living in a house the size of an average family. Or apartments, with nursing staff working around the clock to provide living assistance, giving customers a convenient and secure living space and a comfortable and barrier-free daily life. After a preliminary understanding, I realized that compared to Taiwan, the development of group housing in Japan is more prosperous, and because the government adopts a "government subsidy, private operation" approach in the implementation of group housing welfare policies, it not only provides operating subsidies to private operators , and also provide consulting services and other assistance to the industry to make this social welfare industry more common in the country, so it was decided to further explore this policy.